Analysis of relative rate of reaction/process - Mianowski, Andrzej; Siudyga, Tomasz (Journal of thermal analysis and calorimetry, 2012)
Kinetic or rather thermokinetic analysis of thermal decomposition with releasing gaseous products is a current subject of discussion in many works and still devotes much attention to the property and meaningfulness of the single kinetics triplet determination. Analysis of thermogravimetric data by the relative rate of reaction/process were used to examine the frequently studied process of thermal dissociation of calcium carbonate as a model compound and comparing with published data for chemically defined compounds (azo-peroxyesters) and complex polyolefins–liquid paraffin mixtures. Two methods of correlation between parameters of the model were observed: thermodynamic and analytical expression. It was shown that these relations depend on course of the process. For analyzed model substance, enthalpy of reaction can be deduced on the basis of relation between coefficients in three-parameter equation. For large values of coefficients it is not possible, but other type of correlation was proved. Also, the relative rate of CO 2 gasification (Boudouard reaction) of brown and bituminous coals was analyzed and compared to that of its pyrolysis.